Analisis Pola Rantai Pasok dan Kinerja Rantai Pasok Agroindustri Kelanting di Kabupaten Pesawaran dan Kabupaten Pringsewu (Studi Kasus Agroindustri Kelanting Darwiyanto dan Agroindustri Kelanting Robbani) - Anna Dwi Putri; Ktut Murniati; Adia Nugraha (Politeknik Negeri Lampung, 2020)
This study aims to analyze the supply chain model and supply chain performance kelanting agroindustry in Pesawaran District and Pringsewu District. This research was conducted at Agroindustry Kelanting Darwiyanto in Karang Anyar Village, Gedong Tataan Subdistrict, Pesawaran District and Agroindustry Kelanting Robbani in Mataram Village, Gading Rejo Subdistrict, Pringsewu District. Data collection was conducted on November-December 2019. The supply chain model used analysis descriptive method. Supply chain performance in the kelanting agroindustry is measured using indicators used in measuring the performance of cassava into kelanting based on the SCOR (Supply Chain Operation Reference). Supply chain performance measurements were made by comparing indicators FoodSCOR Card indicators, which consist, input indicators and output indicators. The results showed the flow pattern of supply chain started from farmers and collectors as the main suppliers of raw materials, agroindustry, kelanting wholesalers, kelanting retailer and consumers. Supply chain performance showed that input indicators were good and output indicators were deficient based on FoodSCOR Card comparison indicators.